On spectral stability problem for a pair of self-adjoint elliptic differential operators on bounded open sets - Burenkov, Victor; Tuyen, Bien Thanh (Eurasian Mathematical Journal, 2019)
We prove estimates for the variation of the eigenvalues for a pair of self-adjoint elliptic differential operators in the case of diffeomorphic open sets.